Creatine kinase-deficient hearts exhibit increased susceptibility to ischemia-reperfusion injury and impaired calcium homeostasis. - Spindler, M; Meyer, K; Strömer, H; Leupold, A; Boehm, E; Wagner, H; Neubauer, S (2004)
The creatine kinase (CK) system is involved in the rapid transport of high-energy phosphates from the mitochondria to the sites of maximal energy requirements such as myofibrils and sarcolemmal ion pumps. Hearts of mice with a combined knockout of cytosolic M-CK and mitochondrial CK (M/Mito-CK(-/-)) show unchanged basal left ventricular (LV) performance but reduced myocardial high-energy phosphate concentrations. Moreover, skeletal muscle from M/Mito-CK(-/-) mice demonstrates altered Ca2+ homeostasis. Our hypothesis was that in CK-deficient hearts, a cardiac phenotype can be unmasked during acute stress conditions and that susceptibility to ischemia-reperfusion injury is increased because of altered Ca2+ homeostasis. We simultaneously studied LV performance and myocardial Ca2+ metabolism in isolated, perfused hearts of M/Mito-CK(-/-) (n = 6) and wild-type (WT, n = 8) mice during baseline, 20 min of no-flow ischemia, and recovery. Whereas LV performance was not different during baseline conditions, LV contracture during ischemia developed significantly earlier (408 +/- 72 vs. 678 +/- 54 s) and to a greater extent (50 +/- 2 vs. 36 +/- 3 mmHg) in M/Mito-CK(-/-) mice. During reperfusion, recovery of diastolic function was impaired (LV end-diastolic pressure: 22 +/- 3 vs. 10 +/- 2 mmHg), whereas recovery of systolic performance was delayed, in M/Mito-CK(-/-) mice. In parallel, Ca2+ transients were similar during baseline conditions; however, M/Mito-CK(-/-) mice showed a greater increase in diastolic Ca2+ concentration ([Ca2+]) during ischemia (237 +/- 54% vs. 167 +/- 25% of basal [Ca2+]) compared with WT mice. In conclusion, CK-deficient hearts show an increased susceptibility of LV performance and Ca2+ homeostasis to ischemic injury, associated with a blunted postischemic recovery. This demonstrates a key function of an intact CK system for maintenance of Ca2+ homeostasis and LV mechanics under metabolic stress conditions.